The Relationship between LBW History and Genetic Factors with the Incidence of Toddler Stunting at Loa Ipuh Health Center Tenggarong - Ernawati, Rini; Feriani, Pipit; Khosyi, Nida Dzakiyah (Jurnal Ilmu Kesehatan, 2022)
Stunting in toddlers in Indonesia is still an important nutritional problem that needs to be the focus of attention. Toddler stunting occurs due to nutritional consumption disorders that occur over a long period of time and can occur since the womb. The problem that can occur in stunting toddlers is that it can result in growth and development disorders such as impaired thinking processes, low immunity, the long-term impact is that they can suffer from heart disease, diabetes and even stroke, this situation will result in humans becoming unproductive, and can threaten the future generation of the nation. This study aims to determine the relationship of LBW history and genetic factors with the incidence of stunting in toddlers in the working area of the loa ipuh tenggarong health center. This study used a descriptive correlational research design with a cross sectional approach. The total sample size was 175 respondents, research instruments using questionnaires, data analysis with the chi-square test. The results of the study on the LBW history variable obtained a p value = 0.000, meaning the p value < (0.05) so that Ho is rejected, meaning that there is a relationship between LBW history and the incidence of stunting, and the genetic factor variable obtained a p value = 0.000, meaning the p value < (0.05) Ho is rejected, so it is said that genetic factors are associated with the incidence of stunting in toddlers. The conclusion is that the history of LBW and genetic factors of maternal height have an impact on the birth of babies whose growth is disturbed, so it is necessary to monitor maternal health since adolescence and pregnancy. Keywords: LBW, Genetic, Stunting, Toddler.